2011
DOI: 10.1093/ndt/gfr357
|View full text |Cite
|
Sign up to set email alerts
|

Remission of proteinuria and preservation of renal function in patients with renal AA amyloidosis secondary to rheumatoid arthritis

Abstract: Regardless of histological severity, intensive therapeutic intervention that includes strict inflammatory control and optimal control of hypertension may change the histology-predicted prognosis of RA-associated renal AA amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Indeed, the SAA protein level reached its baseline value at 3 months after tocilizumab treatment, 2 months after the remission of nephrotic syndrome. Given that the development of nephrotic-range proteinuria related to amyloidosis often requires a much longer duration [11], these results suggest that the effects of tocilizumab on nephrotic-range proteinuria can be partly directed toward another pathophysiology, as observed in the present case.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Indeed, the SAA protein level reached its baseline value at 3 months after tocilizumab treatment, 2 months after the remission of nephrotic syndrome. Given that the development of nephrotic-range proteinuria related to amyloidosis often requires a much longer duration [11], these results suggest that the effects of tocilizumab on nephrotic-range proteinuria can be partly directed toward another pathophysiology, as observed in the present case.…”
Section: Discussionsupporting
confidence: 55%
“…Because increased production of IL-6 plays an important role in the synthesis of SAA proteins [16], it is reasonable to consider that the active control of the serum IL-6 concentration at a lower level is a promising treatment strategy for preventing the progression of amyloidosis secondary to RA. Indeed, previous studies have reported that treatment with anti-IL-6 receptor antibodies decreases the SAA level and mitigates RA-related amyloidosis [10,11]. These results indicate that in the present case, from an ethical point of view, we did not perform the additional renal biopsy to confirm the reduction or disappearance of amyloid deposition in the glomeruli.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Compared to Tuglular, et al 23 , Hazenberg and Rijswijk 24 noted a higher rate of hypertension (20% to 35%) in their study on AA amyloidosis. In another article, 8 of 9 female patients with rheumatoid arthritis and AA amyloidosis had hypertension 25 . It might be that the conflicting results arise, in part, from misdiagnosing NAKD as AKD, based on clinical grounds alone.…”
Section: Rheumatologymentioning
confidence: 99%
“…Ülkemizde yapılan bir çalışmada da amiloidoz tanısı alan hastalarda FMF, tüberküloz, bronşiektazi ve romatoid artritin daha sık olduğu bildirilmiştir (15). Portekiz ve Japonya'da proteinürisi olan romatizmal hastalarla ilgili 16 ve 9 hastalık sekonder amiloidoz olgu bildirimleri olmuştur (16,17). Hopfer ve ark.…”
Section: Kaynaklarunclassified